Trust women to choose: A response to John a Robertson's ‘Egg freezing and Egg banking: empowerment and alienation in assisted reproduction’ - Goold, I (Oxford University Press, 2017)
In ‘Egg Freezing and Egg Banking: Empowerment and Alienation in Assisted Reproduction’, John A Robertson responds to the American Society of Reproductive Medicine's statement that oocyte preservation should no longer be considered an experimental treatment. He explores the implications of this development, focusing on the potentially empowering impact of oocyte preservation as a means for women to preserve their fertility. He also engages with concerns about the possibility that such a development may raise issues of alienation. He highlights some of the potential problems that may emerge as women gain the capacity to store and either donate or sell any eggs they do not need for their own reproductive purposes. Much of his paper is valuable and considered, but in places, his views rest on assumptions about women's attitudes to their fertility, understanding of the technology, and relationship with their gametes that are open to dispute. This paper teases out some of these assumptions and puts pressure on them by drawing on the growing body of data about what women actually do think and feel about fertility issues. It focuses on two of his main concerns—that social egg freezing may give women a false sense of security and that women may be harmed if a market in eggs leads to their alienation from their gametes. Via this response to Robertson, I aim to redress the tendency often seen in discussions around women, infertility, aging, and empowerment to unquestioningly accept what I argue are stereotypes and assumptions about women's views and capacity to reason.